Pemberdayaan Guru RA Kota Salatiga dan Kabupaten Semarang untuk Meningkatkan Mutu Pembelajaran - M. Agung Hidayatulloh; Urifatun Anis (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
Some teachers of Islamic Kindergarten (RA) in Salatiga and Semarang District realize that there is still little absorbed information related to the preparation of instructional media. Even so, not many of them have high motivation to take a reflective action such as implementing a Classroom Action Research. This service activity that in the form of training of creating educative props (APE) and training on preparing the design of PTK aims to facilitate the teachers to achieve pedagogical and professional competence as well as achieve quality learning. The results show that both the preparation of media and the design of PTK will be more focused if using a reference; in this case the base is six child development scopes as set forth in Permendikbud No. 137 of 2014 on National Education Standards of Early Childhood.